If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8 = -4 + 2x Solving -8 = -4 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -8 + -2x = -4 + 2x + -2x Combine like terms: 2x + -2x = 0 -8 + -2x = -4 + 0 -8 + -2x = -4 Add '8' to each side of the equation. -8 + 8 + -2x = -4 + 8 Combine like terms: -8 + 8 = 0 0 + -2x = -4 + 8 -2x = -4 + 8 Combine like terms: -4 + 8 = 4 -2x = 4 Divide each side by '-2'. x = -2 Simplifying x = -2
| y=9x^2+9x+84 | | -2(-3)(6)(-8)= | | -7+x=-6x+70 | | 5x+4z=11 | | 10x+29=6x+5 | | -6a=110 | | 3x+11=22 | | -8+4u=-24 | | 9g=30 | | 2x+x+8+x=180 | | 4(x-4)=2(x-19) | | 8x-3(4x+2)=6 | | 9t-6-6-6t=6 | | 9t-6-66t=6 | | x^2-100x+2100=0 | | 3(4x+3)=2x+5(3-x)+2 | | -3y=25 | | -3x^2-22x-12=0 | | 4y-6=26+8 | | 18+-6(5x-8)=-24 | | -3=35 | | 3y=35 | | -3x-y=-4 | | y=14x-12 | | 6(x-3)=3(x+9) | | X-3(X+10)=12 | | 1K-8+2k=4 | | 6y-3(y+2)=3(y-2) | | 3(6+5*-4)=2(-5+4*-4) | | 4.5(b+1)-2=49(b+3) | | 4x-5+2x=31 | | -16=5x-10+9 |